2014
DOI: 10.1039/c4fo00052h
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect and prostate gene expression profiling of steryl ferulate on experimental rats with non-bacterial prostatitis

Abstract: Steryl ferulate (SF) is a bioactive mixture extracted from rice bran and shows higher inhibitory activity against inflammation than the corresponding free sterols. In this study, the aim was to investigate the anti-inflammatory effect and prostate gene expression profiling of SF using a Xiaozhiling-induced non-bacterial prostatitis (NBP) rat model. The anti-inflammatory effect was evaluated by prostate weight, prostate index, acid phosphatase, density of lecithin corpuscles (DLC), white blood cell count (WBC),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…γ‐Oryzanol, a mixture of steryl ferulates (esters of plant sterols with ferulic acid), has gained great interest due to its bioactive properties. In various studies, γ‐oryzanol has been reported with cholesterol lowering , antioxidant , anti‐inflammatory , and anti‐carcinogenic effects , which are responsible for the health benefits of the whole rice grain. The varying profiles in bioactive lipids within rice may suggest different health benefits of rice.…”
Section: Introductionmentioning
confidence: 99%
“…γ‐Oryzanol, a mixture of steryl ferulates (esters of plant sterols with ferulic acid), has gained great interest due to its bioactive properties. In various studies, γ‐oryzanol has been reported with cholesterol lowering , antioxidant , anti‐inflammatory , and anti‐carcinogenic effects , which are responsible for the health benefits of the whole rice grain. The varying profiles in bioactive lipids within rice may suggest different health benefits of rice.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental animals were divided into 2 groups: saline group and xiaozhiling group. Following abdominal surgery, the prostate was exposed and injected with 0.1 ml of normal saline or an equal volume of xiaozhiling respectively as described (22). One month later, rats were anesthetized with intraperitoneal injection of pentobarbital sodium, and prostate tissue was excised by abdominal surgery.…”
Section: Rat Model Of Nonbacterial Prostatitismentioning
confidence: 99%
“…The experimental animals were randomly divided into 2 groups: saline group and xiaozhiling group. Following abdominal surgery, the prostate was exposed and injected with 0.1 ml of normal saline or an equal volume of xiaozhiling respectively as described [22]. One month later, rats were anesthetized with intraperitoneal injection of pentobarbital sodium, and the prostate tissue was excised by abdominal surgery.…”
Section: Rat Model Of Nonbacterial Prostatitismentioning
confidence: 99%